2021
DOI: 10.1186/s12903-021-01960-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary oral mucosa-associated lymphoid tissue (MALT) lymphoma in patient with monoclonale gammopathy: a rare case report

Abstract: Background Monoclonal gammopathy is a biological reality encountered in approximately 1% of the general population. In the absence of clinical and biological signs, it is considered of undetermined significance; however, it can be a biological signature of a monoclonal lymphocytic or plasma-cell proliferation. Their localisation to the oral mucosa remains rare and difficult to diagnose, particularly in indolent forms that escape imaging techniques. Case presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The cumulative probability of MGUS progression to MM or related disorders was 10% and 25% at 10 years and 20 years, respectively. [ 19 ] Another report showed that MGUS was present for 13 years at the time of diagnosis of MALT lymphoma, [ 20 ] despite MGUS did not transform into MM.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative probability of MGUS progression to MM or related disorders was 10% and 25% at 10 years and 20 years, respectively. [ 19 ] Another report showed that MGUS was present for 13 years at the time of diagnosis of MALT lymphoma, [ 20 ] despite MGUS did not transform into MM.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Barone S et al, the most commonly involved sites are in the soft tissues of oral cavity, with an incidence rate presenting as 38.4%, 19.2%, and 11.5% for buccal mucosa, tongue and gingiva [ 44 ]. As for the clinical appearance, lymphoma occurring in the gingiva, buccal mucosa, and palate usually manifests as ulceration (Table 2 ) [ 39 , 45 56 ], while that of FL has been discussed above, and masses or nodular lesions may be observed or palpated under the mucosa of the palate, buccal, and tongue [ 39 , 45 , 50 , 51 , 57 60 ]. Swelling of the lip, palate, gingiva, or buccal mucosa may serve as alternative oral signs of lymphoma [ 61 64 ].…”
Section: Discussionmentioning
confidence: 99%